Koalas, Kiwis and Kangaroos: The Challenges of Creating an Online Australian Cultural Dictionary for Learners of English as an Additional Language - Miller, Julia; Kwary, Deny A.; Setiawan, Ardian W. (Lexikos, 2017)
This article reports on an online cultural dictionary for learners of English as an Additional Language (EAL) in Australia. Potential users studying English for academic purposes in an Australian university pre-entry program informed each stage of the dictionary’s creation. Consideration was given to the need for such a dictionary; terms to be included; information necessary for each entry (including audio and visual material); use of a limited defining vocabulary; example sentences; notes on each term’s usage; and evaluation of user feedback once the dictionary had been launched online. Survey data indicate that users particularly value the dictionary’s ease of use, example sentences, and specifically Australian content (including pronunciation given in an Australian accent). It is suggested that more entries be added, and that cultural dictionaries be created for other varieties of English, as well as for other languages.